Parents’ Use of Complementary Health Approaches for Young Children with Autism Spectrum Disorder. - Lindly, Olivia J.; Thorburn, Sheryl; Heisler, Karen; Reyes, Nuri M.; Zuckerman, Katharine E. (Journal of Autism & Developmental Disorders, 2018)
Knowledge of why parents use complementary health approaches (CHA) for children with autism spectrum disorder (ASD) is limited. We conducted a mixed methods study to better understand factors influencing parents’ decision to use CHA for ASD. Parent-reported data about CHA use were collected on a probability sample of 352 young children with ASD in Denver, Colorado; Los Angeles, California; or Portland, Oregon. Follow-back interviews were conducted with 31 parents. CHA use was negatively associated with older child age and positively associated with parents’ belief ASD has major consequences, living in Portland or Denver, and medication use. Nine themes help explain these results. Study findings may have utility for healthcare providers working with children with ASD and their families regarding CHA.